Systemic inflammation in acute intermittent porphyria: a case–control study. (15th December 2016) - Storjord, E.; Dahl, J. A.; Landsem, A.; Fure, H.; Ludviksen, J. K.; Goldbeck‐Wood, S.; Karlsen, B. O.; Berg, K. S.; Mollnes, T. E.; W. Nielsen, E.; Brekke, O.‐L.
Summary: This study aimed to examine whether acute intermittent porphyria (AIP) is associated with systemic inflammation and whether the inflammation correlates with disease activity. A case–control study with 50 AIP cases and age‐, sex‐ and place of residence‐matched controls was performed. Plasma cytokines, insulin and C‐peptide were analysed after an overnight fast using multiplex assay. Long pentraxin‐3 (PTX3) and complement activation products (C3bc and TCC) were analysed using enzyme‐linked immunosorbent assay (ELISA). Urine porphobilinogen ratio (U‐PBG, µmol/mmol creatinine), haematological and biochemical tests were performed using routine methods. Questionnaires were used to register AIP symptoms, medication and other diseases. All 27 cytokines, chemokines and growth factors investigated were increased significantly in symptomatic AIP cases compared with controls ( P < 0·0004). Hierarchical cluster analyses revealed a cluster with high visfatin levels and several highly expressed cytokines including interleukin (IL)‐17, suggesting a T helper type 17 (Th17) inflammatory response in a group of AIP cases. C3bc ( P = 0·002) and serum immunoglobulin (Ig)G levels ( P = 0·03) were increased significantly in cases with AIP. The U‐PBG ratio correlated positively with PTX3 ( r = 0·38, P = 0·006), and with terminal complement complex (TCC) levels ( r = 0·33, P = 0·02). PTX3 was a significant predictor of the biochemical disease activity marker U‐PBG in AIP cases after adjustment for potential confounders in multiple linear regression analyses ( P = 0·032). Prealbumin, C‐peptide, insulin and kidney function were all decreased in the symptomatic AIP cases, but not in the asymptomatic cases. These results indicate that AIP is associated with systemic inflammation. Decreased C‐peptide levels in symptomatic AIP cases indicate that reduced insulin release is associated with enhanced disease activity and reduced kidney function. Abstract : This case‐control study examined systemic inflammation in patients with acute intermittent porphyria (AIP), and whether the inflammation correlated with the disease activity markers delta‐aminolevulinic acid (ALA), porphobilinogen (PBG) and porphyrins. Reduced prealbumin indicate inflammation in the liver, and decreased C‐peptide levels in symptomatic AIP cases indicated that reduced insulin release was associated with enhanced disease activity and reduced kidney function. Organ damage may activate complement measured as increased levels of the terminal complement complex (TCC) and C5a which activates cells to release cytokines, interleukins and growth factors.